A functional approach in an elite sport performance centre: from the movement assessment to the injury prevention using a new testing protocol - Gargagli, M.; Baudry, T. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: According to the observations conducted in an elite sport performance centre, 71% of athletes experience injury during the sporting season. Joining the centre implies an increase of training load, thereby elevating the risk of injury [1]. Additionally, downtime due to injuries is significantly linked with a decrease in performance [2]. We aimed to characterise the functional capacities of athletes to better prevent the occurrence of injury. METHODS: Four hundred and fifty French elite athletes from thirteen sports development programmes participated in this three-year retrospective study. Each athlete was evaluated through the Mobility and Stability Screen (M2S), a functional assessment consisting of thirteen exercises (seven exercises were lateralised). The binary notation system led to a twenty-point score. Each athlete was evaluated twice: at the beginning and at the end of the season. Corrective protocols of five exercises performed at least three times a week were set up for each athlete, aiming at improving an anatomical location mobility or stability. Injury reports were collected by the centre` doctors, reporting 1353 de-identified injuries. Functional tests` scores and blinded injury reports were analysed considering different variables: sport, status (new or old in the structure), moment of the season and injuries details. RESULTS: The average M2S score was 9.54±4.06 over 20 points. Sport (Kruskal-Wallis-chi-squared=115.23; p=2.2e-16) and status (F=12.12;p=5.67e-05) had a significant impact on the M2S score. Rugby league achieved the lowest scores (6.77 ± 2.66), while aerobic received the highest scores (16.15 ± 3.05). New athletes had an average score two points lower than old athletes. Each athlete increased their mean score by two points between pre-test and post-test (F-value=1.73;p=0.10) on the body part trained as part of the routine protocol (Z-value=4.76;p=1.94e-06). Considering location, 54% of the injuries were located on the lower limbs, 23% on the upper limbs, 23% on the back, head and trunk. September, October and November concentrated 46% of all injuries, representing the riskiest period. Finally, logistic regression showed that athletes with less than 10 points had a 76% chance of being injured, while those with more than 15 points had a 50% chance of being injured. CONCLUSION: Various factors could influence the functional score of each athlete. However, the progression of the M2S score over the season showed that the routines and regular training were effective in developing functional qualities and that high functional scores led to a significant decrease in the probability of injury.